Performance of photosynthetic pigments, according to regrowth age after grazing Pennisetum purpureum cv. Cuba CT-115 in the rainy season - Fortes, Dayleni; Herrera, Rafael Segundo; Gonz?lez, Sayonara; Garc?a, M.; Romero, Aida; Cruz, Ana M. (Cuban Journal of Agricultural Science, 2010)
Through completely randomized deign with fifteen repetitions, the effect of the regrowth age (30, 45, 60, 75, 90, and 105 d) after grazing Pennisetum purpureum cv. Cuba CT- 115 on the content of green pigments and carotenoids was studied during the rainy season, as well as the relations of the chlorophyll a (Cla) and the age with regrowth yield. The lowest content (P < 0.001) of Cla, chlorophyll b (Clb) and carotenoids was found at 30 d of regrowth (2.07, 0.71 and 0.49 mg/dm2, respectively). The highest (P < 0.001), for Cla, Clb and carotenoids, was obtained at 105 d (3.04, 1.81 and 0.57 mg/dm2, respectively). The sum of the chlorophylls had the same pattern of response as that of the chlorophylls, but the ratio (Cla/Clb) was higher (P < 0.001) at 30 d. For chlorophylls /carotenoids, the highest value was attained at 105 d of regrowth. An equation of multiple regression was obtained to link the yield of the regrowth with the age and the Cla (R2= 0.91, P < 0.01). It was concluded that in the conditions of this study, the contents of photosynthetic pigments increased with the age and a multiple linear regression was obtained between the age of regrowth, the Cla and the regrowth yield. Key words: chlorophyll a, chlorophyll b, carotenoids, age, Pennisetum purpureum vc. Cuba CT-115.